Plant Microbes Symbiosis: Applied Facets - Arora, Naveen Kumar Arora (Springer, 2015)
Plant associated microorganisms (PAMs) play a number of very important roles to better the life of their host plant. It is believed that the origin of plant microbe interactions is as old as the arrival of plants on land, and both the mutual partners selected each other after a long evolutionary process. These useful microbes provide the plants with nutrients, battle pathogens, combat abiotic stresses, and can play several other roles in the plant ecosphere. Plant microbe interactions in tandem can perform acts such as reclamation of bar ren soils, degradation of recalcitrant pollutants, and removal of dangerous compounds from the ecosystems.